Embankment breaching at Indian Sundarban – an assessment on altered primary sediment index properties and fluvial flow parameters. Issue 4 (2nd October 2022) - Chaudhuri, Susanta; Das, Vikas Kumar; Debnath, Koustuv; Hansda, Sunil
ABSTRACT: Failure of manmade embankments at the islands of Sundarban estuaries, India recur almost annually and results in the submergence of fertile agricultural land and claim human lives. Field studies were carried out to investigate the primary index properties of the embankment soil collected from three locations at the concave bends of embankment in the Sundarbans area. A correlation is drawn between alteration of natural layout of embankment soil and modification of its index properties following the traditional construction of embankment. Close introspection of embankment soil under scanning electron microscope were carried out to understand the spatial variations of the susceptibility of soil grains towards erosion for different layers of the embankment sediments. The flow velocities at permissible closest vicinity to river facing embankment wall were much higher than estimated threshold velocities for the entrainment of soil grains and resulted in the formation of undercuts at the basal part of the embankments that triggered its breaching. Finally, from the analyses of obtained results, some preventive measures are recommended to retard the rate of embankment breaching processes which may be expected to provide more sustainability to the erected embankments and will reduce the chances of frequent disasters at the Indian Sundarbans.